A non-PCR SPR platform using RNase H to detect MicroRNA 29a-3p from throat swabs of human subjects with influenza A virus H1N1 infection1. Issue 13 (7th July 2015) - Loo, Jacky F. C.; Wang, S. S.; Peng, F.; He, J. A.; He, L.; Guo, Y. C.; Gu, D. Y.; Kwok, H. C.; Wu, S. Y.; Ho, H. P.; Xie, W. D.; Shao, Y. H.; et al.
<x xml:space="preserve">Abstract</x> A new non-PCR assay platform using RNase H to detect MicroRNA 29a-3p from patients' throat swabs with influenza A virus H1N1 infection.